2023
DOI: 10.3390/molecules28114491
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Review of the Action Mechanisms of Berberine, Quercetin and Silymarin on Insulin Resistance/Hyperinsulinemia and Cardiovascular Prevention

Abstract: Insulin resistance (IR) and the associated hyperinsulinemia are early pathophysiological changes which, if not well treated, can lead to type 2 diabetes, endothelial dysfunction and cardiovascular disease. While diabetes care is fairly well standardized, the prevention and treatment of IR lacks a single pharmaceutical approach and many lifestyle and dietary interventions have been proposed, including a wide range of food supplements. Among the most interesting and well-known natural remedies, alkaloid berberin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 222 publications
0
4
0
Order By: Relevance
“…Silymarin has various beneficial metabolic effects, including serving as a PPAR-gamma agonist, improving the sensitivity of the insulin receptor type 1 substrate, increasing the activity of PI3K, Nrf2, and Akt, increasing the expression of GLUT4 on the cell surface and inhibiting HMG-CoA reductase [ 195 , 196 ]. Silymarin has demonstrated choleretic activity by generating upregulation of the bile salt export pump [ 197 , 198 ].…”
Section: Molecules With Demonstrated Clinical Efficacy In the Prevent...mentioning
confidence: 99%
“…Silymarin has various beneficial metabolic effects, including serving as a PPAR-gamma agonist, improving the sensitivity of the insulin receptor type 1 substrate, increasing the activity of PI3K, Nrf2, and Akt, increasing the expression of GLUT4 on the cell surface and inhibiting HMG-CoA reductase [ 195 , 196 ]. Silymarin has demonstrated choleretic activity by generating upregulation of the bile salt export pump [ 197 , 198 ].…”
Section: Molecules With Demonstrated Clinical Efficacy In the Prevent...mentioning
confidence: 99%
“…It is contained in many plants including Coptis Chinensis. There is a large amount of scientific literature that supports the fact that berberine has favorable effects on cardiovascular risk factors such as hypercholesterolemia, hyperglycemia, arterial hypertension and insulin resistance ( 62 65 ).…”
Section: Tratment Of Ir/hyperinsmentioning
confidence: 99%
“…In the RELAX study, it was shown that subjects with HFpEF and DM had similar levels of NT-ProBNP compared with nondiabetics, but markedly higher levels of the vasoconstrictor endothelin-1 (ET-1), of markers of inflammation such as uric acid and C-reactive protein, and of profibrotic markers such as valectin-3 and carboxy-terminal telopeptide of collagen type 1 [34]. It is well known that the alterations of these parameters are also characteristic of IR/Hyperin states [35]. Echocardiographically, patients with HF and DM had a significantly abnormal LV diastolic function as shown by higher E/e' ratio, with increased LVM and reduced exercise tolerance compared with subjects with HF without DM [36].…”
Section: Insulin Resistance/hyperinsulinemia and Chronic Heart Failurementioning
confidence: 99%
“…From the analysis of experimental in vitro and in vivo studies, it clearly appears that these three substances reduce IR and consequent circulating elevated insulin levels. Therefore, these substances could protect the evolution toward overt type 2 diabetes and the development of cardiovascular abnormalities [35]. Both quercetin and silymarin have extensive literature that support their efficacy in counteracting IR/Hyperins and LVH development, and in preventing cardiovascular alterations [57][58][59][60][61][62][63][64][65].…”
Section: Berberinementioning
confidence: 99%